2006
DOI: 10.1164/rccm.200512-1835oc
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin Decreases Oxidative Stress in Lung Fibroblasts Exposed to Cigarette Smoke

Abstract: We conclude that clusterin may have a protective effect against cigarette smoke-induced oxidative stress in lung fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…It has previously been reported that cigarette smoke induces oxidative stress in human lung fibroblasts, which may then initiate a process of repair and collagen deposition [41]. Furthermore, the interaction between fibroblasts and inflammatory cells may also play a role in fibrotic remodeling.…”
Section: Structure Of the Small Airways In Established Copdmentioning
confidence: 99%
“…It has previously been reported that cigarette smoke induces oxidative stress in human lung fibroblasts, which may then initiate a process of repair and collagen deposition [41]. Furthermore, the interaction between fibroblasts and inflammatory cells may also play a role in fibrotic remodeling.…”
Section: Structure Of the Small Airways In Established Copdmentioning
confidence: 99%
“…To further analyze the role of the AhR in inflammation, we exposed primary lung fibroblasts from AhR Ϫ/Ϫ as well as from AhR ϩ/Ϫ and AhR ϩ/ϩ mice to increasing concentrations of CSE for 24 h and measured PG production by enzyme immunoassay. The use of CSE for in vitro assessment of tobacco smoke exposure is well described (9,18,44,51,52). Basal levels of immunoregulatory and proinflammatory PGs, namely PGE 2 ( Fig.…”
Section: Characterization Of Ahr Protein Expression and Function In Ahrmentioning
confidence: 99%
“…In the multistep process of carcinogenesis, cigarette smoke may act during the initiation and promotion phases of lung carcinogenesis, triggering a cascade of events [3,27]. The target tissue for gases and particles is the tracheo-bronchial epithelium, which acts as a mechanical barrier [10] and is the ideal region for studying the toxicity of inhaled substances [28]. In particular, cigarette smoke can induce cytotoxicity, increased detachment of cells, DNA strand-breaks, apoptosis and increased cell proliferation [20,26,29].…”
Section: Introductionmentioning
confidence: 99%